filmov
tv
Conversion of propositional logic sentence to conjunctive normal form (PL to CNF) - example 4
![preview_player](https://i.ytimg.com/vi/38QGUyV8dSA/maxresdefault.jpg)
Показать описание
This video is a part of series on Propositional Logic.
Example:
¬(A⊕B)→C ≡ ((not (A xor B)) implies C )
To see the layout of the series, follow the link bellow:
I Had a Crack at it is a personal blog that contains notes on Maths, Electronics and Informatics.
Example:
¬(A⊕B)→C ≡ ((not (A xor B)) implies C )
To see the layout of the series, follow the link bellow:
I Had a Crack at it is a personal blog that contains notes on Maths, Electronics and Informatics.